2011
DOI: 10.1007/s10620-011-1758-z
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Juice Prostaglandins and Peptide Growth Factors as Potential Markers of Chronic Atrophic Gastritis, Intestinal Metaplasia and Gastric Cancer: Their Potential Clinical Implications Based on this Pilot Study

Abstract: BackgroundGastric secretion can provide valuable information especially when Helicobacter pylori (Hp) infection results in chronic atrophic gastritis (CAG) and intestinal metaplasia (IM) preceding adenocarcinoma (AdCa).AimsLooking for a potential biomarker of malignant transformation in the setting of chronic inflammation we studied the levels of prostaglandin E2 (PGE2), as well as peptide growth factors [epidermal growth factor (EGF) and transforming growth factor α (TGFα)], harbingers of injury and repair, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…EGF was detected in the serum, plasma, urine and gastric juice of patients with gastric cancer, while analysis of the malignant ascites revealed only very low EGF levels (Chuang et al 1994; Dias et al 2011; Dragovich et al 2006; Han et al 2009; Park do et al 2014; Yasumoto et al 2011; Zhang et al 2014). Several studies indicated an association with advanced disease, metastatic disease and poor prognosis (Czyzewska et al 2009; Hirayama et al 1992; Onda et al 1990; Tahara et al 1986; Yasui et al 1988), while in early gastric cancers, per trend a smaller percentage of EGF-positive tumours was reported (Aoyagi et al 2001; Hirayama et al 1992; Onda et al 1990; Tahara et al 1986; Yasui et al 1988).…”
Section: Resultsmentioning
confidence: 99%
“…EGF was detected in the serum, plasma, urine and gastric juice of patients with gastric cancer, while analysis of the malignant ascites revealed only very low EGF levels (Chuang et al 1994; Dias et al 2011; Dragovich et al 2006; Han et al 2009; Park do et al 2014; Yasumoto et al 2011; Zhang et al 2014). Several studies indicated an association with advanced disease, metastatic disease and poor prognosis (Czyzewska et al 2009; Hirayama et al 1992; Onda et al 1990; Tahara et al 1986; Yasui et al 1988), while in early gastric cancers, per trend a smaller percentage of EGF-positive tumours was reported (Aoyagi et al 2001; Hirayama et al 1992; Onda et al 1990; Tahara et al 1986; Yasui et al 1988).…”
Section: Resultsmentioning
confidence: 99%
“…TGF-α is upregulated in certain types of human cancer. Several studies demonstrated that overexpression of growth factors in the gastric mucosa was implicated in the pathogenesis of gastric cancer (26) and gastric cancer cells grew in response to EGF/TGF-α activation of the EGFR in an autocrine loop (27).…”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 and gastrin activate EGF-R and trigger the mitogen-activated protein kinase pathway stimulating cell renewal and mucosal repair preventing the progression of the chronic atrophic gastritis to metaplasia and ultimately adenocarcinoma of the stomach [41,44]. It has been demonstrated that gastric PGE 2 , EGF, and TGF-α can be tested in patients with already proven chronic atrophic gastritis, as these potential markers may be helpful to identify the disease progression to gastric adenocarcinoma during follow-up visits [45]. Furthermore, gastric EGF and its salivary component are powerful protective factors in patients with Zollinger-Ellison syndrome facing abnormally very high rate of gastric acid secretion [13].…”
Section: Growth Factorsmentioning
confidence: 99%
“…Prostaglandins are produced from arachidonic acid metabolism produced by the stomach and duodenum through the cyclooxygenase (COX) enzymes [45,49,50]. Cyclooxygenase-1 (COX-1) is notably involved in the gastric functional responses such as increase in the blood flow and decrease in the acid secretion even after barrier disruption [32••, 50, 51].…”
Section: Prostaglandinsmentioning
confidence: 99%